A Survey on the association of glycosylated hemoglobin A1C and hyperlipidemia in patients with type 2 diabetes - musavi, hadis; Mahdiannasser, Mojdeh; Shamshirian, Amir; Azizi, Soheil (Archives of Medical Laboratory Sciences, 2019)
Background: Type 2 diabetes includes a series of disorders characterized by hyperglycemia, which are followed by dysfunction in insulin secretion. In the clinical laboratory, A1C test defines blood glucose levels over a three-month period. The aim of this study is to evaluate the correlation between HbA1c and hyperlipidemia in patients with type 2 diabetes. Materials and Methods: An cross-sectional study was performed on 209 diabetic patients men (n=109) and women (n=100) with a mean age of 57.1 ± 11.1 years. Diagnosis of diabetes was performed according to the WHO criteria. In this study, venous blood (5 ml) was collected from participants after overnight fasting, and HbA1C levels and lipid profiles were determined using enzymatic methods and auto-analyzer device. Risk factor values (TCH/HDL-C) and atherogenic index of plasma (AIP) (logTG/HDL-c), as well as LDL-C/HDL-C ratio, were calculated. Results: HDL-C and TCH / HDL-C were significantly increased in women. On the other hand, LDL-C/HDL-C and HbA1c levels were significantly higher in men. There was no significant difference in the levels of cholesterol, triglyceride, fast blood sugar (FBS), LDL-C, and AIP between women and men. Cholesterol, FBS, LDL-C and LDL-C/HDL-C also showed a significant direct correlation with HbA1c, but no significant correlation was observed between triglyceride, HDL, AIP, and risk ratio with HbA1c. Conclusion: HbA1c may be considered as a biomarker for dyslipidemia screening in patients with type 2 diabetes